Optimalisasi Event Wisata Sebagai Penggerak Ekonomi Lokal: Studi Kelembagaan Dan Strategi Pengembangan Pariwisata Di Kuala Jambi - BAHRI, ZAINUL; Aprilianti, Vinni Aprilianti (Jurnal Khazanah Intelektual, 2025)
This study analyzes tourism event development strategies for strengthening the local economy in Kuala Jambi Subdistrict, Tanjung Jabung Timur Regency. Employing a qualitative approach with primary data (FGDs involving researchers, Jambi University academics, Regional Development Planning Agency, Youth-Sports-Culture-Tourism Office, Regional Secretariat’s Economic and Development Division, Research and Development Agency, Cooperative Office, Trade and Industry Office; in-depth interviews with Tourism/Culture/Trade Division Heads) and secondary data (Regional Tourism Development Plan, strategic documents, annual reports from Tourism and Trade/Industry/Cooperative Offices), fieldwork was conducted from July to September 2024. Findings reveal three flagship annual events: Bedak Sejuk Duano Festival (showcasing Duano ethnic cosmetics traditions), Kampung Laut Festival (highlighting mangrove crab harvesting), and Anak Pesisir Festival (coastal children’s cultural games), alongside the national-scale Kenduri Swarnabhumi event (2022) which significantly boosted MSME revenues. SWOT analysis identified core strengths in cultural uniqueness (score 3.875/4) and institutionalized community participation (with government grant support), but critical weaknesses included inadequate infrastructure, limited human capital, and ineffective promotion (score 2.625). Key opportunities centered on digitalization and private partnerships (score 3.25), while primary threats involved destination competition and climate vulnerability (score 3.63). Priority strategies derived from the SWOT matrix: 1)Leveraging cultural assets for ecotourism-based product diversification and digital promotion; 2)Addressing weaknesses through capacity-building training, infrastructure upgrades, and homestay development (9 registered units); 3)Penta-helix collaboration (government-community-private sector-academia-media) for event sustainability. Critical policy recommendations include: establishing a Tourism Collaborative Forum, institutionalizing technical mentorship with sustained grant allocation, integrating infrastructure into the Regional Medium-Term Development Plan, and fostering MSME-private partnerships for product certification. Keywords: Tourism Events, Local Economy, Pentahelix, Community Participation, SWOT Analysis